IMPLEMENTATION OF PROVIDING MEDICINES INFORMATION TO PATIENTS AT THE SEMARANG CITY SUB-PRIMARY HEALTH CENTERS - Setianingrum, Rossa Yuliani; Ikhsan, Muhammad; Nahak, Martinus; Suwarni, Sri; Indrasari, Ferika (Lux Mensana: Journal of Scientific Health, 2024)
Introduction. Providing medicines information is necessary to improve patient compliance and therapeutic efficiency. Limited knowledge regarding the correct use of medicines may lead to medication errors. The purpose of this study was to determine the implementation of providing medicines information at the Semarang City sub-primary health centers. Method. This study is a descriptive non-experimental study with a cross-sectional method. Sampling of patients by accidental sampling with samples of sub-primary health centers was conducted by simple random sampling, consisting of 17 sub-primary health centers. The independent variables in this research are respondents characteristics, while the dependent variables include medicine name, preparation, dosage, usage, storage, indications, contraindications, side effects, stability, and medicine interactions. Data collection was conducted observationally through an observation sheet containing a list of medicines information as specified in Regulation of the Minister of Health and Human Rights No. 74/2016 concerning Pharmaceutical Service Standards at the Health Center. Data analysis was conducted descriptively. Result & Analysis. The results indicated that the majority of medicines information was provided by non-pharmacy personnel (71%). The most common medicines information conveyed was dosage, how to use, and medicines indications. There were three sub-primary health centers with moderate levels of implementation of medicines information provision with 61.7%, 60%, and 33.7%, respectively. Discussion. The implementation of medicines information provision to patients in Semarang City sub-primary health centers has not been fully implemented. The most common components of medicines information include dosage, how to use, and indication, while the least common are medicines name, medicines preparation, storage, side effects, contraindications, stability, and medicines interactions.